[PP.13.14] QUALITY OF LIFE MEASURED BY SF-36 DID NOT CHANGE DURING SIX MONTHS AFTER STARTING ANTIHYPERTENSIVE MEDICATION. (September 2016) - Kantola, I.; Johansson, J.; Kantola, T.; Varis, J.
Abstract : Objective: To clarify the change in quality of life during six months after starting the antihypertensive treatment in hypertensive patients. Design and method: The patients were non-treated and participated during the years 1999–2002 in a six-month study where their antihypertensive treatment was titrated during six months according to a predetermined schedule to reach the target pressure. SF-36 questionnaire was filled out every six weeks by 88 patients (49 females and 39 males, aged 55.4 (7.8), 36–71 years). After six months they used at least one antihypertensive agent. Blood pressure was measured every six weeks by using 24 hour ambulatory measurement. Results: Daytime systolic blood pressure (SBP) decreased from 144.8 (11.6) to 129.8 (10.1) mmHg (p = 0.001) and diastolic blood pressure (DBP) from 94.1 (7.0) to 82.2 (6.4) mmHg (p = 0.001). Nocturnal SBP decreased from 128.5 (12.8) to 113.2 (10.3) mmHg (p = 0.001) and DBP from 77.9 (7.8) to 67.4 (6.9) mmHg (p = 0.001). Daytime heart rate (HR) changed from 72.7 (9.5) to 72.0 (8.3) beats/min (p = 0.09) and nocturnal HR decreased from 62.0 (7.8) to 60.5 (6.7) beats /min (p = 0.001). None of the eight SF-36 parameters nor their mean value changed significantly during the six months of the study. The change in physical functioning and role physical were negatively explained by daytime SBP in the beginning, in bodily pain negatively by daytime SBP and nocturnal HR at the end, in general health negatively by 24 hour SBP in the beginning, in role emotional negatively by daytime SBP at the end. Vitality, social functioning and mental health were explained by none of the parameters. The mean of the parameters of SF-36 questionnaire was explained negatively by daytime SBP in the beginning. Conclusions: According to our results quality of life did not change significantly during the six months after starting antihypertensive medication although blood pressure decreased significantly. Low change in the SF-36 physical parameters was mostly explained by high systolic blood pressure in the beginning of the study. Mental SF-36 parameters were not explained by any of the measured parameters.